Konseling Alat Kontrasepsi Terhadap Tingkat Pengetahuan dan Sikap Ibu Hamil Trimester III di UPT Puskesmas Kalampangan Kota Palangka Raya: Counseling Contraceptive Devices on the Level of Knowledge and Attitude of Third Trimester Pregnant Women at UPT Puskesmas Kalampangan Palangka Raya City - Herlinadiyaningsih Herlinadiyaningsih; Greiny Arisani; Seri Wahyuni (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Family planning is an effort to regulate the desired number and spacing of children. Based on the proportion of postpartum family planning services in Indonesia, 67.5% of new postpartum women use contraception more than 42 days after delivery, 20% after returning from health facilities up to 42 days after delivery, 7.3% concurrent with the delivery process and as many as 5.2 % after delivery is complete but have not returned from the health facility. This study used a pre-experimental. The research sample for third trimester pregnant women (gestational age 28-42 weeks) in the Work Area of ​​the Puskesmas Kalampangan Kota Palangka Raya who met the inclusion criteria was 33 respondents. Characteristics of the majority of respondents lack of knowledge (57,5%), good attitude (54,5%), aged 20-35 years (78,8%), middle education (42,4%) and high school (42,4%), not working (72,7%), multigravida (66,7%) and giving birth in a health facility (78,8%). The average level of effectiveness before counseling was 56,3 and after counseling was 79,7 then the mean attitude before counseling was 21.3 and after counseling was 24.0. The results of the analysis concluded that there was effectiveness of family planning counseling on the level of knowledge (p-value 0.000) and attitude (p-value 0.000) of third trimester pregnant women at UPT Puskesmas Kalampangan, Palangka Raya City. There needs to be readiness of health workers, especially midwives in providing family planning counseling to pregnant women and an increase in the ability/competence of officers in conducting counseling.